Reaksi Investor atas Laporan Keberlanjutan: Keberagaman Gender Direksi dan Independensi Direksi sebagai Variabel Moderasi - Wisman, Redilla; Triwacananingrum, Wijaya (E-Jurnal Akuntansi, 2021)
The Triple Bottom Line approach makes the company start to consider its non-financial reports as an added value for its stakeholders. moderating gender diversity and independent directors. The study used judgment sampling in sampling. The number of samples is 132 data from industrial sector companies and mineral resources in the 2018 - 2020 SGX. The data analysis technique in this study uses multiple linear regression. Investor reactions are measured based on cumulative abnormal returns with an event span of seven days. Sustainability reports are measured by reference to the standard GRI index. The results show that the quality of sustainability reports has no significant effect on investor reactions, the gender diversity of directors is not significant in strengthening the relationship between sustainability reports and investor reactions, and the independence of directors plays a significant role in strengthening the relationship between the quality of sustainability reports and investor reactions. Keywords :  Investors’ Reaction; Sutainability Report; Board Gender Diversity; Board Independence.